Discovery of novel Cyclophilin D inhibitors starting from three dimensional fragments with millimolar potencies. Issue 23 (1st December 2019) - Grädler, Ulrich; Schwarz, Daniel; Blaesse, Michael; Leuthner, Birgitta; Johnson, Theresa L.; Bernard, Frederic; Jiang, Xuliang; Marx, Andreas; Gilardone, Marine; Lemoine, Hugues; Roche, Didier; Jorand-Lebrun, Catherine
Graphical abstract: Highlights: 6 Cyclophilin D crystal structures with SPR binding confirmed fragment hits having millimolar potencies were discovered. One fragment was merged with a potent reference Cyclophilin D inhibitor resulting in single-digit nanomolar potency. A second fragment provided the basis for replacing the urea linker in the reference inhibitor scaffold by an oxalyl group. Two fragment hits bound in the S1′ and S2 pockets were linked via an amide group resulting in submicromolar potencies. Abstract: Fragment-based screening by SPR enabled the discovery of chemical diverse fragment hits with millimolar binding affinities to the peptidyl-prolyl isomerase Cyclophilin D (CypD). The CypD protein crystal structures of 6 fragment hits provided the basis for subsequent medicinal chemistry optimization by fragment merging and linking yielding three different chemical series with either urea, oxalyl or amide linkers connecting millimolar fragments in the S1′ and S2 pockets. We successfully improved the in vitro CypD potencies in the biochemical FP and PPIase assays and in the biophysical SPR binding assay from millimolar towards the low micromolar and submicromolar range by >1000-fold for some fragment derivatives. The initial SAR together with the protein crystal structures of our novel CypD inhibitors provide a suitable basis for further hit-to-lead optimization.